Pituitary Action of E2 in Prepubertal Grass Carp: Receptor Specificity and Signal Transduction for Luteinizing Hormone and Follicle-Stimulating Hormone Regulation - Qin, Xiangfeng; Xiao, Yaqian; Ye, Cheng; Jia, Jingyi; Liu, Xiangjiang; Liang, Hongwei; Zou, Guiwei; Hu, Guangfu (Frontiers in Endocrinology, 2018)
Estradiol (E2) is onean important sex steroid produced by ovary and brain. In mammals, E2 plays an important role in hypothalamus-pituitary-gonad axis to regulate puberty onset, however, little is known about the functional role of E2 in teleost pituitary. Using prepubertal grass carp as model, three nuclear estrogen receptors (nERs: ERα, ERβ1&ERβ2) and two G protein-coupled estrogen receptors (GPER1: GPER1a&GPER1b) were isolated from grass carp pituitary, . tissue Tissue expression distribution analysis indicated that both nERs and GPERs were highly detected in grass carp pituitary, which suggested that E2 should play an important role in grass carp pituitary. Using primary cultured grass carp pituitary cells as model, high-throughput RNA-seq was used to we scanexamine the E2-induced differential gene expressioned genes (DEGs)after E2 treatment by using RNA-Seq. Transcriptomic analysis showed that E2 could significantly up-regulate the expression of 28 genes in grass carp pituitary cells, which were characterized into different functions including reproduction, gonad development and central nervous system development. Further studies confirmed that E2 could induce LH and FSH secretion and mRNA expression in prepubertal grass carp pituitary in vivo and in vitro. At In the pituitary cell level, LH and FSH regulation by E2 were mediated by both ERβ and GPER1. Apparently, E2-indcued LHβ and FSHβ mRNA expression were mediated by AC/cAMP/PKA, PLC/IP3/PKC, and Ca2+/CaM/CaMK-II pathways. In addition to LH and FSH, E2 could also induce GREB1 (a novel regulator for pituitary development) mRNA expression in grass carp pituitary cells. These results, as a whole, suggested that E2 could played an important role in gonadotropin hormone release and pituitary development in prepubertal grass carp.